Individual Physician versus Team-Based Medical Encounters: Maximizing the Efficiency of a Medical Relief Service in Rural Honduras. (5th July 2011) - Whitney, Rachel; Stevens, Michael; Bearman, Gonzalo
Abstract : Background . For several years, the Virginia Commonwealth University (VCU) Department of Internal Medicine has traveled to the towns of La Hicaca and Coyoles in rural Honduras. In 2010, a new encounter method was employed during the brigade in Coyoles. Objectives . To examine the differences in clinical encounters and adherence with chronic diseases and public health screening between the traditional and team-based encounter methods. Methods . Chi-square analysis was used to determine statistical significance between encounter methods over several variables used in the standard interview form. Results . 314 patients were interviewed using the team-based approach, and 153 patients were interviewed with the traditional model. Statistically significant increases in compliance using the team-based method were observed with diabetes screening and selecting candidacy for antihelminthic therapy. Other variables with significantly increased compliance using the team-based method were compliance with checking a blood glucose value, diagnosing GERD, and prescribing medication such as analgesics and multivitamins. Conclusion . Our results show a statistically significant increase in compliance with data collection and clinical screening using the new team-based encounter method. This design provides a more goal-oriented approach to the patient interview. These data will help guide more effective delivery of health care on future medical relief trips to Honduras.